The monetary value of marine environmental change - Hasselström, Linus (KTH, Miljöstrategisk analys (fms), 2016)
The marine ecosystems are fundamental for human welfare. A number of current environmental pressures need attention, and the formulation of management strategies requires information from a variety of analytical dimensions. The linkage between environmental change and resulting implications for human welfare is one such dimension. This thesis presents studies on welfare implications from hypothetical future policies which improve the state of the marine environment. The method for these studies is economic valuation. The studied scenarios concern eutrophication in the Baltic Sea (including the Kattegat) and oil spill risk from shipping in the Lofoten-Vesterålen area in the Arctic Barents Sea. The thesis shows that the economic benefits from undertaking policies to improve or protect the marine environment in these cases are substantial and exceed the costs of taking measures. In addition to providing new monetary estimates, the thesis also provides new insights concerning 1) what type of scenario to use when valuing an environmental improvement and 2) whether there may exist trade-offs between precision in estimates and the level of ambition with respect to survey instrument complexity and econometric models when conducting valuation studies. The findings suggest an end of an era for studies in which the environmental change is unspecified or based on a single environmental indicator while the actual consequences of the suggested measures are more multifaceted. In contrast, relevant scenarios to study are well-specified and holistic. The thesis further reveals that it might not always be worth the effort to go for the most advanced scenario presentation or statistically best-fitting model specifications. This is something that needs to be further discussed among practitioners in order to allocate valuation resources wisely and not waste resources on unnecessarily elegant valuation studies. QC 20161011